دور الجمعیات النسائیة اللیبیة فی ترسیخ المواطنة1951-1969 - نهایة صالح (University of Mosul-college of Basic Education, 2023)
ABSTRACT Women societies began in Libya with the dawn of united Libyan kingdom in the 1950s of twentieth century . These societies were associated with voluntarily charity deeds based on principles of Islam . They focused on building cultural skills and abilities for libyan females , help them to learn , think , fight illiteracy and poverty throgh enrolling young women in illiteracy programs , in addition to national awareness programs in radio , press , symposiums and charity fairs they used to organize .These societies focused on acknowledging Libyan national identity as colonizing force attempts to erase ; The societies also supported women who wanted to begin small develoment projets to enhance level of Libyan famiy , kill poverty and need in society . Despite the difficulties they faced in that stage , the opposing opinions regarding the work and education of women , these societies contributed in strengthening values of citizenship with their political , economical , social and cultural aspects Keywords education , awareness , renaissance , development , women , patriotism